Implementation of Finite State Automata to Simulation of Automatic Clothes-Folding - Lediwara, Nadiza; Heikmakhtiar, Aulia Khamas; Bimorogo, Sembada Denrineksa; Ahmed, Alfian Habib; Agusti, Rizki Yulian (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
Inconsistencies and differences clothes-folding methods are often a major problem in the military. Everyone has thier method to fold and their method is still traditional. Besides, the neatness of the clothes in the military is emphasized. This method certainly took up their time and energy then the folding was different to each other. To solve this problem, a simulation machine is made to fold the clothes automatically. This system works using Finite State Automa type Non-Deterministic Finite Automata. Finite State Automata are used because they are simple and do not require storage space. The result of this research is a design of an automatic clothes-folding that can be implemented properly and correctly for UNHAN RI’s students. This automatic clothes-folding has succeeded to create consistent folds even though user tried with different clothes.